Effects of pulsed electric field on Escherichia coli ATCC 8739 inactivation, metal migration and physicochemical properties of goat milk - Mohamad, Azizah (2021)
The increasing demand and interest in goat milk worldwide have evolved many studies on the nutritional and functional properties of goat milk. The typical pasteurization method for goat milk is thermal pasteurization. However, thermal pasteurization can cause many unwanted changes such as browning of milk due to Maillard reaction, increase in titratable acidity, degradation of lactose producing formic and lactic acid, decrease in pH, protein and lactose content and precipitation of calcium. Thus, promising non-thermal processing such as pulsed electric field (PEF) has gained greater attention in the food and drink industry, as a substitute for thermal pasteurization due to the rising demand for high nutritional value and fresh-like characteristic of goat milk. This study aims to evaluate the inactivation of Escherichia coli ATCC 8739, physicochemical properties of PEF-processed goat milk and investigate the possibility of the metal migration effect from the electrode material of PEF. In this study, raw goat milk was processed with a laboratory-scale PEF system with continuous mode, monopolar square-wave pulses and fixed pulse width. This model only allows the selection of electric field strength (EFS) and processing time parameters, while the remaining parameters were predetermined by the PEF system, with the maximum EFS and processing time at 40 kV/cm and 13 µs respectively. Therefore, the EFS of 20, 30 and 40 kV/cm for 5 and 10 μs processing time were used to determine the effect of PEF on physicochemical properties of goat milk (pH, titratable acidity, total soluble solids, viscosity, particle size distribution, colour, vitamin A (as β-carotene), B-group vitamin (thiamine (B1), riboflavin (B2) and niacin (B3)), fatty acid profiles and metal migrations). However, it was found that the data were insufficient to be fitted to the inactivation models of Escherichia coli (E. coli) by PEF. Hence, the additional parameters (EFS: 25 and 35 kV/cm; processing time: 7 and 13 μs) were included in the study. The results indicated that PEF-processed goat milk at 40 kV/cm for 10 μs had the lowest pH (6.53 ± 0.03) and the highest titratable acidity (0.21 ± 0.01) value of the samples due to the decrease in calcium ion (Ca2+), which leads to the protonation of the phosphate. The specific surface area (SSA) value significantly increased (p < 0.05) with the increase of PEF processing time. Whereas, PEF processing has shown to reduce 0.03 – 0.06% of the total saturated fatty acids (ΣSFAs) and 8.32 – 51.11% total polyunsaturated fatty acids (ΣPUFAs) of goat milk, while total monounsaturated fatty acids (ΣMUFAs) were increased ranging from 0.02 – 0.05%. Mean concentrations of heavy metals (Fe, Cr, Mn and Ni) in all PEF-processed samples were within the permissible limit of heavy metals according to the USFDA drinking water quality standard. The retention value for vitamin A as β-carotene in PEF-processed samples were between 99.90 – 99.99% with only 0.01 – 0.1% destruction. While the retention value for B-group vitamin were between 95.37 – 98.26% (thiamine), 97.65 – 98.65% (riboflavin) and 98.44 – 99.29% (niacin). The fitting performance for the Weibull and Peleg model was observed to be more accurate and good fits to the observed data of the inactivation kinetics of E. coli by PEF processing, as a function of time and EFS respectively. However, the maximum inactivation level of E. coli by PEF in this study was 3.87 log10 CFU/mL at 40 kV/cm for 13 µs, below the requirements set by the FDA (minimum of 5 log10 CFU/mL). Thus, PEF processing would be recommended as a complementary method to conventional thermal pasteurization. By combining PEF with mild thermal pasteurization (< 55 °C) as a hurdle processing technique, the microbial stability and safety of goat milk can be obtained at the minimum intensity of PEF.